Personality traits and mental distress after COVID-19 testing. Prospective long-term analysis in a Viennese cohort - Guttmann-Ducke, Claudia; Klinger, Sonja; Ziesche, Rolf; Otzelberger, Bernd; Idzko, Marco; Ponocny, Armin; Prantl, Simon Gabriel; Ponocny-Seliger, Elisabeth (Frontiers in Psychiatry, 2023)
Background Symptoms of mental stress are a hallmark of the COVID-19 pandemic. We hypothesized that just testing for COVID-19 could act as an effective stressor for persisting symptoms of mental distress including posttraumatic stress disorder. Our study aimed to determine whether personal beliefs on individual control and competence (locus of control, LoC) correlate with symptoms of mental distress and positive screening for post-traumatic stress disorder during a 9-month observational period. Methods Between March and December 2021, we applied online versions of the Questionnaire on Competence and Control Expectations (FKK), the Depression, Anxiety, and Stress Score (DASS), the Short Screening Scale for DSM-IV Posttraumatic Stress Disorder (PTSD), and a medical history questionnaire for COVID-19 symptoms (visit 1). 48 hours after negative COVID-19 testing, DASS was repeated to address relief effects on mental distress (visit 2). Following 90 days (visit 3), development of mental distress was addressed by a combination of DASS and PTSD, while the possible long-term manifestation of PTSD was evaluated 9 months later (visit 4). Results At visit 1, 7.4 percent of the total sample (n = 867) demonstrated a positive screening for PTSD, while after nine months (at visit 4), 8.9 percent of the remaining sample (n = 204) had positive screening results. The mean age was 36.2 years; 60.8% were women, 39.2% men. In contrast to individuals with negative PTSD screening, these participants demonstrated a significantly different LoC personality profile. This was confirmed by the results of both DASS and the COVID-19 medical history questionnaire. Conclusion Following testing for COVID-19, individuals with positive long-term PTSD screening present with significantly different personality traits than those w/o suggesting that self-confidence and effective control over one’s own actions serve as a protective function against mental distress.